Proses Clipping pada Map Game Online RPG menggunakan Algoritma Cohen-Sutherland - permana, silvester dian handy (Universitas Trilogi, 2018)
Nowadays, online games is the media for interaction with another people in the world. In this game, players are presented in the virtual world. This virtual world displayed on a graph of realism that have various shapes fact as houses, roads, walls, fences, etc. Players in this online game will also be given an avatar of the identity and the realization of the players in the virtual world. Virtual world in the online RPG game certainly require a lot of graphics realism in the viewport windows virtual but certainly not to display the virtual world as a whole. This is because the views of the players who became avatar certainly made equal to the real-world view of the player. In presenting part of the virtual world certainly requires clipping of the map which is a manifestation of the virtual world. Clipping technique used to use Cohen-Sutherland algorithm. This algorithm makes clipping as nine areas where the viewport window will be the main focus in the map and displayed on the screen viewport. This would blur the eight other areas that cannot be seen directly in the viewport. This study provides a view of the same players as in the real world that is played online games can provide a real experience to his players.